Methodology of register analysis: computer-mediated communication - Radić-Bojanić, B. (Лексикографічний бюлетень, 2006)
The paper lists arguments in favour of compiling an annotated CMC corpus by illustrating
how it could be used in the description of the methodology of register analysis, where such a corpus would be immensely useful. In addition, the paper lists some problems which will have to be dealt with during the compilation of such a corpus and states that they will have to be overcome if linguists want to conduct a thorough and detailed analysis.